Discolouration of polyamide microcrystalline denture base plates after exposure to filter cigarette smoke - Jubhari, Eri Hendra; Dangkeng, Zulkarnain Wahid; Dangkeng, Effendy (Padjadjaran Journal of Dentistry, 2019)
Introduction: Denture users with smoking habit often complain about colour changes in their dentures, especially on the base part. Polyamide microcrystalline is a thermoplastic denture base material and does not undergo many colour changes. The purpose of this study was to analyse the effect of filter cigarettes smoke exposure on the colour of polyamide microcrystalline materials. Methods: This study used posttest only control group design — Plate-Shaped sample with a size of 2 x 2 x 0.5 cm3. Nine samples as controls were immersed without exposure to the cigarette smoke, and 9 samples were immersed in artificial saliva with exposure to the filter cigarette smoke by six cycles, where one cycle was in the form of smoke exposure from one cigarette at 30-minute intervals. Cigarette exposure lasts for 21 days using a smoking simulation tool. Every seven days of exposure, colours were evaluated using a DSLR camera. The photos were then analysed with Adobe™ Photoshop in the CIELab colour space. The results were analysed afterwards by a one-way ANOVA variant test, and advance difference tests were analysed using a Post-Hoc test. Results: There was a significant colour change after exposure (p < 0.05), but the control group did not experience discolouration. The highest rate of colour change occurred in the second week, while in the third week the colour changes still occurred but tend to be stable. Conclusion: Exposure to the filter cigarette smoke changes the colour of polyamide microcrystalline denture base.Keywords: Polyamide microcrystalline, filter cigarette smoke, discolouration, denture base